(untitled) (American Journal of Pedagogical and Educational Research, 2024)
In this article has been analyzed the importance of creating conditions for our students regularly and fully enjoy the legacy of the great thinkers of the Uzbek nation about patriotism, for them to mature in a such spiritual environment, and for the humanitarian philosophy and great ideas of the Islamic religion to take a place in the hearts of the young generation. The essence of the importance of educating the young generation growing up today in the spirit of benevolence, generosity, love for the Motherland, patriotism, and a confident view of the future has been revealed.